Correlation of MRI-Evaluated Degenerative Disc Disease with Positivity on Single-Photon Emission Computed Tomography Imaging in Patients with Chronic Low Back Pain - Varga, Michal; Štulík, Jan; Pivarči, Filip; Geri, Gábor; Malík, Jozef; Lang, Otto; Srikandarajah, Nisaharan; Kaiser, Radek (World neurosurgery, 2024)
OBJECTIVE: Chronic low back pain, affecting up to 58% of the population, often stems from intervertebral disc degeneration. Although magnetic resonance imaging (MRI) is commonly used for diagnostics, challenges arise in pinpointing pain sources due to frequent asymptomatic findings. Single-photon emission tomography (SPECT) integrated with computed tomography (CT) offers a promising approach, enhancing sensitivity and specificity. METHODS: In this retrospective study, spanning 2016 to 2022, SPECT/CT imaging was performed on 193 patients meeting specific criteria. We correlated SPECT/CT findings with lumbar MRI results, utilizing Pfirrmann and Rajasekaran classifications for disc degeneration and endplate damage assessment. Logistic regression analysis adjusted for age and sex evaluated associations. RESULTS: Of 965 spinal levels assessed, SPECT/CT positivity strongly correlated with higher Pfirrmann grades and Rajasekaran endplate classifications. Notably, Modic changes (MCs) on MRI displayed a nonsignificant relationship with SPECT/CT positivity. Significant associations were observed in older patients with positive MCs, Pfirrmann grades, and Rajasekaran classifications. CONCLUSIONS: This comprehensive study, the largest of its kind, establishes a significant link between SPECT/CT positivity and advanced lumbar degenerative changes. Higher Pfirrmann grades and increased Rajasekaran endplate damage demonstrated substantial correlations with SPECT/CT positivity. Notably, MCs did not exhibit such association. Our findings underscore the potential of SPECT/CT in identifying pain generators in degenerative spinal conditions, offering valuable insights for future interventions.
Keywords: Magnetic Resonance Imaging; Low back pain; jednofotonová emisní výpočetní tomografie; magnetická rezonanční tomografie; Humans; Chronic Pain; lidé středního věku; Lumbar Vertebrae; SPECT; Female; Aged; dospělí; Single Photon Emission Computed Tomography Computed Tomography; degenerace meziobratlové ploténky; senioři; lidé; Low Back Pain; chronická bolest; Degenerative disc disease; bederní obratle; Adult; Axial pain; SPECT/CT; ženské pohlaví; Male; Middle Aged; Retrospective Studies; lumbalgie; Intervertebral Disc Degeneration; retrospektivní studie; mužské pohlaví; Tomography, Emission-Computed, Single-Photon